Simultaneous resection of pituitary adenoma and clipping of aneurysm through endoscopic endonasal approach: a case report - He, Wenbo; Xu, Chongxi; Zheng, Datong; Jie, Danyang; Xu, Jianguo; Zheng, Songping (Frontiers in Oncology, 2024)
Pituitary adenomas and intracranial aneurysms are prevalent neurosurgical conditions, but their simultaneous presence is uncommon, affecting only 0.5%-7.4% of those with pituitary adenomas. The strategy of treating aneurysms endovascularly before removing pituitary adenomas is widely adopted, yet reports on addressing both conditions at once through an endoscopic endonasal approach (EEA) are scarce. We present a case involving a pituitary adenoma coupled with an anterior communicating artery aneurysm. Utilizing the EEA, we excised the adenoma and clipped the aneurysm concurrently. The patient recovered well post-surgery, with follow-up assessments confirming the successful resolution of both the adenoma and aneurysm. We proved the feasibility of the EEA in the treatment of pituitary adenomas with anterior communicating artery aneurysms under specific anatomical relationships and close intraoperative monitoring.